Did descartes die of poisoning? - Ebert, Theodor (Early Science and Medicine, 2019)
The paper discusses the circumstances of the fatal illness and the death of René Descartes in 1650 at the French embassy in Stockholm. It considers the hitherto available evidence, in particular the main medical documents: two letters, the first written in Dutch by Descartes' servant, Henri Schluter, the second written in Latin by the Dutch doctor Johann van Wullen. English translations of these two documents are given respectively in Appendix 1 and Appendix 3 of this paper. Other documents, letters by the French ambassador, Pierre Chanut, or the report in the Descartes biography by Adrien Baillet, are also discussed. An analysis of the documentary evidence indicates a high probability that Descartes was poisoned with arsenic on two occasions, on February 2nd and again on February 8th, the second poisoning proving to be fatal. The paper then discusses the questions of 'whodunnit' and why.
CRIS-Team Scopus Importer:2019-07-26
Keywords: François Viogué; French Embassy in Stockholm; Johann van Wullen; Medicine; Pierre Chanut; Pneumonia; Poisoning by arsenic; Queen Christina of Sweden; René Descartes